2018
DOI: 10.1016/j.jpainsymman.2017.12.484
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of a Measure of Parent and Child Needs in Pediatric Palliative Care

Abstract: Initial psychometric analysis of the PCNeeds is encouraging, but further study of reliability and validity with more diverse respondents is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
0
22
0
1
Order By: Relevance
“…37 Further, information delivered to parents using medical jargon left parents distressed and requiring further clarification but often felt apprehensive to do so. 23,38,39…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…37 Further, information delivered to parents using medical jargon left parents distressed and requiring further clarification but often felt apprehensive to do so. 23,38,39…”
Section: Resultsmentioning
confidence: 99%
“…50 The experiences of parents with income decline, cost of care and adjustment to their lifestyle changes were reported. 38,39,47 Parents described a dramatic decrease in their income and financial uncertainty as being major problems and reported financial stress. 47 One study reported that 71% of parents interviewed gave up work, decreased their working hours or changed careers to be more flexible in caring for their child.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can also negatively affect the ability and selfefficacy of caregivers, especially mothers. Therefore, anxiety and concern management can be particularly helpful (11). In fact, when parents, especially mothers, feel empowered in a critical condition, they support their sick children and facilitate their treatment process (12).…”
Section: Introductionmentioning
confidence: 99%